Evaluating the reliability and quality of knee osteoarthritis educational content on TikTok and Bilibili: A cross-sectional content analysis - Jiakuan Tu; Chaoxiang Zhang; Hao Zhang; Likan Liang; Jianhua He (Digital Health)
Background Knee osteoarthritis (KOA), a prevalent degenerative joint disease, burdens global health. Amid the digital era, patients increasingly seek KOA-related information on TikTok and Bilibili, but its quality is scarcely studied, raising accuracy, and reliability concerns. Aim To systematically evaluate the reliability and quality of KOA educational videos on TikTok and Bilibili using validated tools (modified DISCERN and Global Quality Score, GQS), and to analyze associations between content quality, uploader types, and user engagement metrics. Methods Using “Knee Osteoarthritis” as the keyword, the top 100 videos from each platform were retrieved. After excluding duplicates and irrelevant videos, 164 were analyzed. Videos were classified by uploader type and content. Two senior orthopedic physicians evaluated their reliability and quality via a modified DISCERN tool and GQS. Nonparametric statistical methods were applied for data analysis. Results Bilibili had a significantly higher proportion of high-quality videos (GQS ≥4: 38.0% vs. 11.8%; DISCERN ≥4: 49.3% vs. 24.7%, P < 0.05). Professional institutions’ videos ranked highest, while TikTok was mostly run by professional uploaders (with medical or healthcare-related qualifications) (98%). Disease knowledge and treatment were the main content types. Engagement metrics were intercorrelated but not with quality scores. Conclusion Bilibili hosted more high-quality KOA videos than TikTok (GQS ≥4: 38.0% vs. 11.8%, DISCERN ≥4: 49.3% vs. 24.7%, P < 0.05), with professional institutions showing the highest reliability. Engagement metrics did not correlate with quality. To mitigate misinformation, targeted strategies—such as platform-specific guidelines for health content and integration of video quality discussions into clinical consultations—are needed.